A 10-step safety management framework for construction small and medium-sized enterprises. Issue 3 (3rd July 2017) - Gunduz, Murat; Laitinen, Heikki
Abstract : It is of great importance to develop an occupational health and safety management system (OHS MS) to form a systemized approach to improve health and safety. It is a known fact that thousands of accidents and injuries occur in the construction industry. Most of these accidents occur in small and medium-sized enterprises (SMEs). This article provides a 10-step user-friendly OHS MS for the construction industry. A quantitative OHS MS indexing method is also introduced in the article. The practical application of the system to real SMEs and its promising results are also presented.